Influence of Recruitment, Organizational Culture and Motivation on Employee Performance in The ABC Banten Health Office - Pancasasti, Ranthy (PT Larva Wijaya Penerbit, 2023)
Background: In an institution, the importance of employee performance as a standard for an institution can be assessed well. Where the performance assessment that occurs at Kantor Kesehatan ABC Banten has decreased due to various factors. So the need to improve this performance needs to be seen its effect on several variables, there are recruitment, organizational culture and motivation, which can improve employee performance in achieving organizational goals. Objective: The purpose of this study is to measure the influence of recruitment, organizational culture, and motivation on employee performance at Kantor Kesehatan ABC Banten. Originality / Value: The novelty in this research is that no previous research has been found that discusses the influence of recruitment, organizational culture, and motivation on employee performance at Kantor Kesehatan ABC Banten. Research Limitations: The limitation of this study is measure the influence of recruitment, organizational culture, and motivation on employee performance at Kantor Kesehatan ABC Banten. Design/methodology/approach: The method used in this research is quantitative and uses a questionnaire with an ordinal scale of 1-10 points. The sampling technique was used the saturated sampling method from 70 samples. Findings: The findings of the study explain that there is an influence of recruitment, organizational culture and motivation on employee performance at Kantor Kesehatan ABC Banten